Proposal Of A Timer Controller With Constant Switching Frequency And Power Factor Correction - Galelli, Marcos T.; Vilela, Márcio S.; Coelho, Ernane A. A.; Vieira Jr., João Batista; de Oliveira, João Carlos; de Freitas, Luiz Carlos; Farias, Valdeir J. (Eletrônica de Potência, 2006)
The proposal of this paper is to introduce a new control technique for power factor correction in acdc converters. It combines the advantages of conventional hysteresis control strategy and the prominent characteristics of constant switching frequency. The fundamental idea consists of determining the ideal time interval that exists between the moment when the input current crosses with the reference current and the converter commutation. Thus the input current can oscillate simetrically around the reference current with constant frequency of operation. The operating principles, theoretical analysis and simulation results on a single-phase Boost converter are presented to validate the proposal.